Updating thermal imaging dataset of hand gestures with unique labels - Yeduri, Sreenivasa Reddy; Breland, Daniel Skomedal; Pandey, Om Jee; Cenkeramaddi, Linga Reddy (Elsevier Inc., 2022)
An update to the previously published low resolution thermal imaging dataset is presented in this paper. The new dataset contains high resolution thermal images corresponding to various hand gestures captured using the FLIR Lepton 3.5 thermal camera and Purethermal 2 breakout board. The resolution of the camera is 160×120 with calibrated array of 19,200 pixels. The images captured by the thermal camera are light-independent. The dataset consists of 14,400 images with equal share from color and gray scale. The dataset consists of 10 different hand gestures. Each gesture has a total of 24 images from a single person with a total of 30 persons for the whole dataset. The dataset also contains the images captured under different orientations of the hand under different lighting conditions.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Thermal imaging; Thermal Camera; Machine learning models; Hand Gestures; Sensor